TEACHER PROFESSIONAL COMPETENCY DEVELOPMENT MANAGEMENT AT MAS AL-WASHLIYAH 22 MEDAN TEMBUNG - Miranda, Nanda; Mardianto, Mardianto; Syaukani, Syaukani (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This research aims to analyze the management of teacher professional competency development at MAS Al-Washliyah 22 Tembung. This research is a type of qualitative research using a descriptive approach. This research was carried out through a qualitative approach using descriptive methods. Data collection using interviews, observation and documentation studies. Data sources are madrasa principals, deputy principals and teachers. Data analysis with data categorization, data interpretation. The research results concluded that first, planning for the development of teacher professional competence has not been contained in strategic plans, operational plans and activity plans, where development activities are still in the form of training and supervision activities. Second, the policy for developing teacher professional competence is also still in the information stage. The policy has not been directed towards training and supervision policies. Third, the implementation of teacher professional competency development begins in February-May in the form of supervision of teaching implementation by the head of the madrasah, while it is carried out by external madrasahs, namely in February-November of the new school year in the form of training from the Madrasah KSKK Directorate which takes part in 15 people while e- Guru.id and the Ministry of Religion have not yet had any teachers participate. Fourth, evaluation of teacher professional competency development is carried out during training only by conveying warnings about the importance of training, while evaluation during supervision is carried out through face-to-face evaluation with each teacher in the field of study and evaluation at work meetings.